The news model of asset price determination: An empirical examination of the Danish football club Brøndby IF - Casper W. Jørgensen; Mark R. Moritzen; Georg Stadtmann (European University Viadrina, Department of Business Administration and Economics, 2012)
According to the news model of asset price determination, only the unexpected component of an information should drive the stock price. We use the Danish publicly listed football club Brøndby IF to analyze how match outcome impacts the stock price. To disentangle gross news from net news, betting odd information is used to control for the expected match outcome.
Keywords: G14; L83; G32; 330; news model; football industry; betting odds; stock market; market efficiency; event study; Börsenkurs; Information; Effizienzmarktthese; Fußballsport; Professioneller Sport; Event Study; Dänemark